The role of SNPs in the α-chain of the IL-7R gene in CD4+ T-cell recovery in HIV-infected African patients receiving suppressive cART - Rajasuriar, R.; Booth, D.R.; Gouillou, M.; Spelman, T.; James, I.; Solomon, A.; Chua, K.; Stewart, G.; Deeks, S.; Bangsberg, D.R.; Muzoora, C.; Cameron, P.U.; et al. (2011)
We previously found an association between faster CD4+ T-cell recovery in HIV-infected patients receiving combination antiretroviral therapy (cART) and interleukin-7 receptor-α (IL-7Rα) haplotype-2 in a predominantly Caucasian cohort. This study aims to determine whether this association was also significant in Africans. Patients were recruited from the Uganda AIDS Rural Treatment Outcomes (UARTO) cohort (n=352). We used survival analysis and linear mixed modelling (LMM) to determine factors associated with CD4 T-cell recovery. Eight IL-7Rα single-nucleotide polymorphisms (SNPs) were genotyped in both Africans and Caucasians (n=57). Soluble (s)IL-7Rα levels were measured by ELISA. In UARTO, IL-7Rα haplotype-2 was associated with slower CD4 T-cell recovery following cART by using survival analysis (P=0.020) and no association was found with LMM (P=0.958). The tagging-SNP for IL-7Rα haplotype-2 (rs6897932) was associated with decreased sIL-7Rα (P<0.001). The haplotypes for the IL-7Rα were significantly different in Africans and Caucasians. Using IL-7Rα genotypes we found slower CD4 T-cell recovery in UARTO patients was still associated with rs6897932 (P=0.009) and rs3194051 was associated with faster CD4 T-cell recovery (P=0.006). Unlike Caucasians, we did not demonstrate a significant association between IL-7Rα haplotype 2 and faster CD4 T-cell recovery in Africans. The IL-7Rα SNPs associated with CD4 T-cell recovery following cART differ in African and Caucasian cohorts.Genes and Immunity advance online publication, 22 September 2011; doi:10.1038/gene.2011.65.